High-gain low-excess-noise MWIR detection with a 3.5-µm cutoff AlInAsSb-based separate absorption, charge, and multiplication avalanche photodiode - Adam A. Dadey; J. Andrew McArthur; Abhilasha Kamboj; Seth R. Bank; Daniel Wasserman; Joe C. Campbell (APL Photonics, 2023)
Mid-wavelength infrared (MWIR) detection is useful in a variety of scientific and military applications. Avalanche photodiodes can provide an advantage for detection as their internal gain mechanism can increase the system signal-to-noise ratio of a receiver. We demonstrate a separate absorption, charge, and multiplication avalanche photodiode using a digitally grown narrow-bandgap Al0.05InAsSb absorber for MWIR detection and a wide bandgap Al0.7InAsSb multiplier for low-excess-noise amplification. Under 2-µm illumination at 100 K, the device can reach gains over 850. The excess noise factor of the device scales with a low k-factor of ∼0.04. The unity-gain external quantum efficiency of the device attains a peak of 54% (1.02 A/W) at 2.35 µm and maintains an efficiency of 24% (0.58 A/W) at 3 µm before cutting off at ∼3.5 µm. At a gain of 850, the device has a gain-normalized dark current density of 0.05 mA/cm2. This device achieves gains more than double that of the state-of-the-art InAs detectors and achieves gain-normalized dark current densities over two orders of magnitude lower than that of a previously reported MWIR Al0.15InAsSb-based detector.